(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The conclusions of the Algebra and Number Theory course "Algebra of Quaternions" are highlighted as a result of a perfect and careful study of the topic, in the process of studying this topic, getting more detailed information about polynomials and information about the use of the quaternion method in algebraic examples. information provided.